Design and implementation of phlorotannin extraction processing technique from seaweed / Chia Shir Reen - Chia, Shir Reen (2019)
Upon the high demand of functional food and health supplement in the recent years, intensive investigation has been conducted by researchers either in academic area or professional field. In this work, the phlorotannin was extracted from brown seaweed using alcohol/salt liquid biphasic system (LBS). Liquid biphasic system is a novel sustainable technique that combined several processes into a step, where the separation and purification of bioactive compounds were completed in a unit operation. Non-toxic solvent was utilized and there was potentiality to recycle the solvent used in the system. The recycled solvent is able to recover similar amount of phlorotannin compared to the new solvent used. Phlorotannin is one of the beneficial bio-products found in brown algae and attracted huge interest of community owing to its health beneficial effect. Hence, the extraction of phlorotannin is lucrative as it has biological activities that can be applied into food, pharmaceutical and cosmeceutical products. The brown algae, Padina australis and Sargassum binderi were capable to recover 76.1% and 91.67% of phlorotannin by using 2-propanol/ ammonium sulphate system, with purification factor of 2.49 and 1.59, respectively. The recycling of salt phase was carried out and total amount of salt (g), 41.04% and 72.39% were recovered for Padina australis and Sargassum binderi, respectively. The system showed good recyclability, as comparable phlorotannin recovery (44.33% and 44.60% for Padina australis, 65.84 and 84.28% for Sargassum binderi) which was observed even twice extractions was performed. The LBS was concluded as an eco-friendly technique that has potential to be upscaled into industrial scale.